Potensi Pencemaran Nama Baik Dalam Gerakan “Naming And Shaming” Bagi Pelaku Tindak Pidana Kekerasan Seksual - Sahid Yudhakusuma Kalpikajati; Riska Andi Fitriono (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2024)
Nowadays, with advances in information technology and the emergence of the internet, people are carrying out the "Naming and Shaming" movement to deal with cases of sexual violence. The way this movement works is by spreading the identity of perpetrators of sexual violence through social media to create a deterrent effect for perpetrators and prevention for society. Unfortunately, this movement has the potential for defamation if the perpetrators are not proven to have committed the crime. Accordingly, this research was conducted to find out the potential for such defamation. By using literature study and data analysis, it was found that the movement was not a form of defamation, because it was used for the public interest. However, it must be accompanied by the ability to prove the perpetrator actually committed sexual violence, otherwise it has the potential to become a criminal act of defamation.